O parque das Missões/RS (1930/2010): patrimônio e esquecimento no Brasil - Thais Almeida Rodrigues (2013)
This work aimed to review the literature and find out how the intangible heritage of the Parque das Missões with regard to the Guarani, that is, how they are being rescued and presented to visitors as the memory of the Rio Grande do Sul, Brazil, first inhabitants.The methodology occurred by content and discourse analysis of bibliographic works and interpretation of legal norms. To achieve the goal, it was necessary to identify the reasons the indigenous memory in Museu/Parque das Missões be silenced. Were perceived three reasons: (1) thru the Jesuits behavior, who judged themselves in the right to 'build' a civilization based on religion and developed a massacre through the organization and imposition of the European culture; (2) due to in any historiographical process throughout the ages the missions built environment was credited solely to the Jesuits, as if the Guarani were just legs and arms, manpower without heads and soul; and (3) due to the silence of Lucio Costa in the evaluation of São Miguel das Missões as immaterial cultural heritage, once he had the power in his hands, but did not use it to rescue the indigenous issue, stressing only the Jesuits, comparing them to the great architects of Antiquity. We conclude that the Guarani are silenced in the Parque Histórico Nacional das Missões, and this not only in the academic vision, but also by the Instituto Nacional do Patrimônio Histórico Nacional and the Ministério da Cultura. However, the duty of memory is the duty to do justice by the memory of an Other one, won and continued muted since the 16th century.